Religion, Media, and Materiality - Jessie Pons (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2023)
This introduction to the Special Issue “Religion, Media, Materiality” succinctly outlines the central themes of media and authority, serving as tertia comparationis within the volume, and evokes their significance in addressing media changes from a transdisciplinary perspective. It surveys three theoretical frameworks and general perspectives on the interplay between religion, media, and authority, as put forth by Stewart Hoover, Birgit Meyer, and David Morgan. The discussion emphasises how the case studies examined by Sarit Shalev-Eyni, Ines Weinrich, Hanna Staehle, Giulia Evolvi, and Tim Karis actively engage with these frameworks. In doing so, they contribute to a more nuanced understanding of the intricate connections between media, authority, and religion, offering a detailed exploration of these overarching concepts.